Actual problems of the Kazakh neology and neography (Eurasian Journal of Philology Science and Education, 2016)
The dynamics of the lexical structure of modern Kazakh literary language is characterized by active introduction of new lexical innovations designed to transfer terminological body of the Kazakh language by using primarily internal potential resources of the national language. Neologisms always were and will remain in sight of linguists, as their emergence in language is a continuous process. It should be noted that new words present a complicated, multiple-valued language and cultural phenomenon. Therefore any problems connected with neologisms are always actual. In this regard it is possible to consider that neology (science about neologisms) and neography (science about the theory and practice of the description of neologisms in dictionaries) intensively develop in Kazakh linguistics. The article based on the study of the theoretical conclusions of foreign and domestic linguists systematizes and summarizes the main provisions of neology and neography, social and linguistic reasons for entering / not entering new words in speech, the analysis of methods and forms of reflection of lexical innovations in the Kazakh lexicography.
Keywords: dictionary structure; lexicology; new words; neology; neography; lexicography; new uses; lexical innovations.